WAYS TO USE WASTE-FREE TECHNOLOGY IN THE PRODUCTION OF SODA PRODUCTS - Mirsalimova Saodat Rakhmatzhanovna; Ibrokhimov Ilkhamjon Ikramjon ugli; Kokanbayev Ikramjon Ibrokhimovich (Galaxy International Interdisciplinary Research Journal, 2023)
The ammonia method of soda production generates a large amount of liquid and smoky gaseous waste. Disinfection of these wastes is an urgent task in the chemical industry. The article recommends using a membrane separator device to extract limestone and separate the burner from exhaust gases to extract carbon dioxide, as well as using sodium hydroxide instead of lime milk to extract ammonia. Such a solution prevents the release of gaseous waste into the environment, and instead of liquid waste, a solution of sodium chloride is obtained, which is reused in production. In addition, the consumption of water, sodium chloride, electricity and fuel is significantly reduced, and the profitability of production increases.